Who's to blame? Causal attributions of the economic crisis and personal control. (November 2017) - Bukowski, Marcin; de Lemus, Soledad; Rodriguez-Bailón, Rosa; Willis, Guillermo B.
In this research, we examined how people cope with threats to personal control related to the global economic crisis. Three studies (one correlational and two experimental) tested the prediction that blaming social outgroups could serve as a means to restore a threatened sense of personal control. We found that outgroup blaming attributions are related to higher levels of personal control over the effects of the economic crisis (Study 1). Further, blaming outgroups helps to restore a sense of personal control (Study 2) only when blaming attributions are related to specific versus global causes (i.e., outgroups but not the economic system; Studies 2 and 3). We discuss individual and social implications of outgroup blaming as a form of coping with lack of control in the context of economic crises.